Metastatic squamous cell carcinoma in a cervical lymph node - Zachary W. Bloomer; Andrea N. Snitchler; Mohamed K. M. Shakir; Thanh D. Hoang (Clinical Case Reports, 2020)
Abstract Cervical lymphadenopathy is a very common complaint for patients presenting to an endocrinology clinic. This case highlights common locations that malignancy presents at as well as their ultrasound characteristics.